Detection of bovine parainfluenza type 3 virus in Iraq: Aida Bara Allawe and Anton Sabri Al-bana - Allawe, Aida Bara (The Iraqi Journal of Veterinary Medicine, 2012)
This study is considered the first study in our country to isolate bovine parainfluenzatype 3 virus (BPIV-3) from naturally infected calves. BPIV-3 virus was isolated from nasalswabs collected from calves with respiratory disease. The virus was isolated and titrated insecondary embryonic bovine kidney (SEBK) cell culture; other cell cultures (secondary sheeptestis and chicken embryos fibroblast cell cultures) were used for propagation of isolatedvirus. Examination of infected cell culture revealed giant cell formation and intracytoplasmicinclusions. The isolated virus agglutinated guinea pig’s erythrocytes and produces clearheamadsorption of guinea pig’s erythrocyte in infected SEBK cell culture. Virus titer was2×102TCID50/0.1ml in the sixth passage and became 2×104.5TCID 50/0.1ml in the ninthpassage. The new isolated virus was identified as BPIV-3 by heamagglutination inhibitiontest, serum neutralization test and indirect immunoflurescent technique, by using specificmonoclonal and polyclonal antibody. The virus was sensitive to ether. High titer of BPIV-3antibodies was detected in sera of infected animals during convalescent period by ELISA test